RITUAL SEBAGAI DAYA TARIK EKOWISATA di DESA NOUNEA KABUPATEN MALUKU TENGAH - Yosevita.Th.Latupapua Satyawan Pudyatmoko,Chafid Fandeli, dan M. Baiquni (Jurnal Kawistara, 2015)
Objects of cultural attractiveness is one product that offers culture of a region in the form of livingculture and culture heritage. as an attraction for tourists. One of the tribes in Seram Island CentralMaluku, which has Naulu tribe culture with a special pattern, both physical and social behavior. Nauluceremonial ritual is a potential appeal of high local culture for tourists, Culture Naulu people in theform of traditional rituals, has a high value for tourists. It is necessary for the study to examine thelocal cultural forms the object of fascination Naulu as ecotourism. The method used to address theobjectives are descriptive qualitative method. Sugiono (2007), suggests that this motede used to examinethe condition of natural objects, where the researcher serves as a key instrument, procedure producesdescriptive data qualitative research in the form of verbal of people and behavior, as well as the observedphenomena. Techniques of data collection is done through observation, in-depth interviews (depthinterview) study of literature and documentation. Inductive data analysis, and research results furtheremphasize the significance of what is observed and not generalizations based on measures of quantity.Based on the results of the observation and identification of local cultural forms that are owned bythe Naulu, it can be said that the various forms of rituals and ceremonies inherited from the lelehurpotential to be developed as a product of cultural attractiveness for tourists. the sanctity of traditionalritual procession is a unique culture that can be packaged as a competitive cultural products for tourists